Characterizing donation behavior from psychophysiological indices of narrative experience - Correa, Kelly A.; Stone, Bradly T.; Stikic, Maja; Johnson, Robin R.; Berka, Chris (Frontiers in Neuroscience, 2015)
Research on narrative persuasion has yet to investigate whether this process influences behavior. The current study explored whether: 1) a narrative could persuade participants to donate to a charity, a prosocial, behavioral decision; 2) psychophysiological metrics can delineate the differences between donation/non-donation behaviors; and 3) donation behavior can be correlated with measures of psychophysiology, self-reported reactions to the narrative, and intrinsic characteristics. Participants (n = 49) completed personality/disposition questionnaires, viewed one of two versions of a narrative while EEG and ECG were recorded, completed a questionnaire regarding their reactions to the narrative, and were given an opportunity to donate to a charity related to the themes of the narrative. Results showed that 1) 34.7% of participants donated; 2) psychophysiological metrics successfully delineated between donation behaviors and the effects of narrative version; and 3) psychophysiology and reactions to the narrative were better able to explain the variance (88% and 65%, respectively) in the amount donated than all 3 metrics combined as well as any metric alone. These findings demonstrate the promise of narrative persuasion for influencing prosocial, behavioral decisions. Our results also illustrate the utility of the previously stated metrics for understanding and possibly even manipulating behaviors resulting from narrative persuasion.